PROFESSIONAL TRAINING IN DEVELOPING KNOWLEDGE OF ART-DESIGN OF FUTURE TEACHERS BASED ON CREATIVE APPROACH - Daniyorova Shahnoza Erkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article professional training of future teachers in the development of art-design knowledge based on the creative approach of students is highlighted.